Designing a Barcode System to Optimize Food Product Production and Distribution Management - Alfi, Rizki; Maryam, Maryam; Nadiyah, Khairun; Mardesci, Hermiza (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
In the digital era, efficient supply chain and inventory management pose significant challenges for Micro, Small, and Medium Enterprises (MSMEs), particularly in the food sector. The use of barcode technology can enhance stock management and product tracking in real-time. However, the adoption of this technology among MSMEs, especially for traditional food products like rendang, remains limited. This study aims to design and implement a Code 128 barcode system for rendang products produced by MSMEs, incorporating information such as product variants, production batch, production date, and expiration date. The research employs a Research and Development (R&D) method, consisting of needs analysis, design, implementation, and evaluation stages. The findings reveal that the designed barcode system improves stock management efficiency, reduces recording errors, and facilitates integration with modern retail systems. Nonetheless, the study is limited to a small scale and encounters challenges related to infrastructure and human resources. To address these limitations, the research proposes solutions such as utilizing more affordable devices and providing training to enhance human resource skills. This study is expected to contribute to the digital transformation of food-sector MSMEs, helping them improve competitiveness in an increasingly challenging market.